2020
DOI: 10.3390/molecules25041017
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Anti-Inflammatory and Immunomodulatory Effects of Dihydroflavones, Flavones, and Flavonols

Abstract: Systemic inflammation, circulating immune cell activation, and endothelial cell damage play a critical role in vascular pathogenesis. Flavonoids have shown anti-inflammatory effects. In this study, we investigated the effects of different flavonoids on the production of pro-inflammatory interleukin (IL) 1β, 6, and 8, and tumor necrosis factor α (TNF-α), in peripheral blood cells. Methods: We studied the whole blood from 36 healthy donors. Lipopolysaccharide (LPS)-stimulated (0.5 μg/mL) whole-blood aliquots wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 52 publications
3
55
0
Order By: Relevance
“…Inhibit production of IL-1β, TNF-α, IL-6, and IL-8 in Lipopolysaccharide-stimulated [122] CVD patients Decrease transcriptional activity of NF-kB [74] Endothelial protection CVD individuals Enhance NO bioavailability, possibly by stimulating eNOS activity [123] 6…”
Section: Healthy Nonsmokersmentioning
confidence: 99%
“…Inhibit production of IL-1β, TNF-α, IL-6, and IL-8 in Lipopolysaccharide-stimulated [122] CVD patients Decrease transcriptional activity of NF-kB [74] Endothelial protection CVD individuals Enhance NO bioavailability, possibly by stimulating eNOS activity [123] 6…”
Section: Healthy Nonsmokersmentioning
confidence: 99%
“…In human monocytes exposed to high glucose concentrations, luteolin significantly reduced IL-6 and TNF-α by inhibiting NF-κB activity [202]. Recently, it was demonstrated that luteolin effectively suppresses IL-1β, TNF-α, IL-6 and IL-8 secretion from PBMC from healthy donors incubated with LPS [203], confirming reports showing that luteolin reduces IL-6 and TNF-α secretion in LPS-stimulated RAW 264.7 macrophages [190]. Hong et al evaluated the anti-inflammatory effects of luteolin in renal I/R injury in Sprague-Dawley rats and demonstrated that this natural compound attenuated serum and renal TNF-α, IL-1β and IL-6, and the renal HMGB1 and NF-κB expression levels in I/R rats [204].…”
Section: Flavanonesmentioning
confidence: 99%
“…Using LPS-stimulated PBMC from healthy subjects, Zaragoza et al demonstrated that naringenin decreases IL-1β, TNF-α, IL-6 and IL-8 production [203]. Hsu et al showed that naringenin extracted from Nymphaea mexicana Zucc.…”
Section: Flavanolsmentioning
confidence: 99%
“…If a microangiopathy and interstitial fluid bound to glycosaminoglycans are present early in lipedema tissue, treatment should aim at supporting the vessels in the legs by the use of the following: compression garments; hands on therapy to move fluid, sodium, and Allen, et al; Women's Health Reports 2020, 1.1 http://online.liebertpub.com/doi/10.1089/whr.2020.0086 other prelymph components out of the tissue into lymphatic vessels; flavonoids and other anti-inflammatories from food and supplements to help reduce inflammation of the microvessels 32 ; and possibly a low-salt diet to decrease glycosaminoglycan content. 31 The data in this article were based on an AVP and collagen spacing that if incorrect as markers of leaky vessels and increased interstitial fluid, respectively, would negate our findings.…”
Section: Discussionmentioning
confidence: 99%